TARI SEBIMBING SEKUNDANG SEBAGAI TARI PENYAMBUTAN TAMU DI KABUPATEN OGAN KOMERING ULU SUMATERA SELATAN - Ani Mandam Dari; RM Pramutomo (Greget, 2021)
This article examines the form of Seguid Sekundang dance presentation in Ogan Komering Ulu Regency, South Sumatra. Problems regarding form are discussed using the theory of R.M Soedarsono in the book Diktat Pengantar Pengetahuan dan Komposisi Tari. This article uses a qualitative research method with descriptive analysis. The collection of data and information is done by observing or observing the object of research, interviews, and literature studies. Sebimbing Sekundang dance was made at the request of Regent Ogan Komering Ulu as as guest welcome dance in 1971. This dance is the result of observations in several sub-districts in Ogan Komering Ulu Regency by combining various cultural forms, especially traditional dance from five tribes (Daye, Komering, Ogan, Ranau, and Semende) in Ogan Komering Ulu Regency.This dance uses properties of a fan, tepak sirih, umbrella, and spear. However, it is the use of distinguishes this dance from the welcoming dance in South Sumatera. The music accompanying the Sebimbing Sekundang dance is another song entitled Ribu-Ribu originating from the Ogan area. Then the arrangement itself by Z. Khusni Karana became the music to accompany the Sebimbing Sekundang dance. This dance reflects the majesty of universe which uses many forms and motifs of plants.Keywords :Form, Analysis of The Movement of The Sebimbing Sekundang Dance.